The Role of Land Deed Officials (PPAT) in Certifying Customary Land - Wijaya, Dwi Julianto; Bawono, Bambang Tri; Hafidz, Jawade (TABELLIUS: Journal of Law, 2023)
This research aims to: (1) To determine and analyze the implementation of registration/certification of customary land in Cirebon Regency. (2) To determine and analyze the role of PPAT in the implementation of registration/certification of customary land. The approach method in this research is sociological juridical. The research specification is analytical descriptive. Data collection tools consist of document or library material studies and interviews. Required data Primary Data and Secondary Data. Primary data was collected through interviews, and (2) secondary data was collected through literature study. Data analysis in this research was carried out qualitatively, that is, the data obtained was compiled systematically and then analyzed qualitatively to explain the problem being studied.1998, as well as Head of BPN Regulation Number 1 of 2006. Keywords: Land; PPAT; Registration.